PENGARUH MODEL INVESTIGASI KELOMPOK TERHADAP KEMAMPUAN MENULIS KARANGAN NARASI KELAS V SD DI KECAMATAN KEJAKSAN KOTA CIREBON TAHUN PELAJARAN 2013-2014 - Abdul Rozak; Mintarsih Danumihardja; - Sariah (Jurnal Tuturan, 2014)
The background of this research is the difficulties of the students in expressing ideas in writing. Research design uses pre-test and post-test control group design, with random sampling. Subject is the class V students of elementary school in Kejaksan Cirebon, object is the ability in writing narrative essay. The number of sample is 72 students. Experiments class is class V students of SDN Kebon Baru I and class control is SDN Kebon Melati II. Instrument of this research is test and observation. Result data of the research is analyzed by using SPSS V. 17.Conclusion (1) learning  process through group investigation model is better  than conventional model based on the increase of pre-test result 63,00 to become 80,39 (2) the activity of experiment class is getting better with the acquisition 97,23 % than the class control 69,45 (3) based on testing group investigation model has p-Value number 0,000. Value 0,000 < level of significant 0,05, and t table (1,70) < t hitung (6,102) means. Ha is accepted and Ho is rejected, it means there is an effect to the group investigation model to the ability of writing narrative essay of class V students.